Sosialisasi Kepedulian Anak Terhadap Lingkungan Di SD Advent Victory Sorong : Anak Cerdas, Peduli Lingkungan - Pattiwael, Maya; Serkadifat, Yetti S.; Turot, Amatus; Malo, Agustinus; Pigome, Andreas; Yeblo, Ely; Singgir, Merlin; Amnan, Nelince (CV. ITTC INDONESIA, 2025)
Tema